2021
DOI: 10.1128/mbio.03169-20
|View full text |Cite
|
Sign up to set email alerts
|

How Phagocytic Cells Kill Different Bacteria: a Quantitative Analysis Using Dictyostelium discoideum

Abstract: Ingestion and killing of bacteria by phagocytic cells protect the human body against infections. While many mechanisms have been proposed to account for bacterial killing in phagosomes, their relative importance, redundancy, and specificity remain unclear. In this study, we used the Dictyostelium discoideum amoeba as a model phagocyte and quantified the requirement of 11 individual gene products, including nine putative effectors, for the killing of bacteria. This analysis revealed that radically different mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
30
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 44 publications
8
30
0
Order By: Relevance
“…These observations confirm that the procedure developed in this study measures accurately and simultaneously bacterial killing and bacterial permeabilization, and that Kil1 and Kil2 are both required for efficient intracellular killing and permeabilization of K. pneumoniae (Figure 4 and Supplementary Figure S4a). lysozyme, the BpiC bactericidal permeability-increasing protein and NoxA, the main superoxide-producing NADPH oxidase in D. discoideum (Jauslin et al, 2021). Genetic inactivation of the corresponding genes led to a slower permeabilization of K. pneumoniae bacteria, although in the original study the defect observed in noxA KO cells was not statistically significant (Jauslin et al, 2021).…”
Section: Kil1 and Kil2 Are Necessary For Efficient Killingmentioning
confidence: 99%
“…These observations confirm that the procedure developed in this study measures accurately and simultaneously bacterial killing and bacterial permeabilization, and that Kil1 and Kil2 are both required for efficient intracellular killing and permeabilization of K. pneumoniae (Figure 4 and Supplementary Figure S4a). lysozyme, the BpiC bactericidal permeability-increasing protein and NoxA, the main superoxide-producing NADPH oxidase in D. discoideum (Jauslin et al, 2021). Genetic inactivation of the corresponding genes led to a slower permeabilization of K. pneumoniae bacteria, although in the original study the defect observed in noxA KO cells was not statistically significant (Jauslin et al, 2021).…”
Section: Kil1 and Kil2 Are Necessary For Efficient Killingmentioning
confidence: 99%
“…Expression of these AMPs in hemocytes may also aid in killing ingested Bacillus subtilis in systemic infection experiments. Phagocytosis and killing of B. subtilis is a phylogenetically ancient process ( 37 ). Of note are genes that are not primarily associated with an immune response, but which may be particularly important, for example, for digesting ingested bacteria ( Vha36-1 ).…”
Section: Resultsmentioning
confidence: 99%
“…pneumoniae by assessing fluorescence extinction following phagocytosis. Previous experiment have shown that the abrupt extinction of GFP fluorescence provides a good estimate of the moment at which ingested bacteria are killed [ 19 ]. Using this method, bacterial fluorescence is extinguished within a few minutes after phagocytosis in WT cells [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous experiment have shown that the abrupt extinction of GFP fluorescence provides a good estimate of the moment at which ingested bacteria are killed [ 19 ]. Using this method, bacterial fluorescence is extinguished within a few minutes after phagocytosis in WT cells [ 19 ]. On the contrary, and in agreement with previous observations [ 11 ], ingested bacteria remained alive for a long time in phg1A KO cells: a typical example is shown, where bacterial killing occurred 60 min after ingestion in phg1A KO cells ( Fig 3A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation